Life in London's changing densities. Issue 10 (25th November 2020) - Blanc, Fanny; White, Tim
ABSTRACT: Despite reaching ever higher densities, London's new residential blocks and towers are evermore exclusive and unaffordable. The current market-led era of high-density housing development contrasts acutely with that of the postwar era, geared around the mass provision of council homes. These changing densities are often discussed at the city level, but there has been little research capturing residents' perspectives. This paper aims to draw parallels between the politics and the experience of density using a recent study focusing on the residents of high-density housing in London. It seeks to demonstrate how consequences of structural shifts – a growing separation between tenures, increasing numbers of transient residents and the escalating role of international finance – impact day-to-day life within these buildings. In so doing, it advocates shifting the prevailing focus on density as a numbers game to considering the issues associated with changing social densities – particularly the inequalities within and between them.